2015
DOI: 10.4018/ijdet.2015010105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Digital Game-Development Approach on Elementary School Students' Learning Motivation, Problem Solving, and Learning Achievement

Abstract: In this study, the game-based development approach is proposed for improving the learning motivation, problem solving skills, and learning achievement of students. An experiment was conducted on a learning activity of an elementary school science course to evaluate the performance of the proposed approach. A total of 59 sixth graders from two classes of the elementary school participated in the experiment. One class of 30 students was selected as the experimental group, and the other class of 29 students was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 49 publications
2
37
0
3
Order By: Relevance
“…These results achieved and expressed in the particular context of this study are in line with other studies that preceded this one. These studies reported that training practices using escape rooms improve student motivation [14][15][16][17], group work [24], activation and participation [31,44], as well as commitment to learning tasks [20,36], which has a close psychological relationship with the absence of a negative effect and adequate attitude of students towards the instructive process [25,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results achieved and expressed in the particular context of this study are in line with other studies that preceded this one. These studies reported that training practices using escape rooms improve student motivation [14][15][16][17], group work [24], activation and participation [31,44], as well as commitment to learning tasks [20,36], which has a close psychological relationship with the absence of a negative effect and adequate attitude of students towards the instructive process [25,45].…”
Section: Discussionmentioning
confidence: 99%
“…Gamification improves various psychosocial academic indicators such as students´motivation, as the activity to be carried out is presented as an attractive challenge for the participants [14][15][16][17][18]. Other benefits found in the literature review are resolution of problems in training activities [19], commitment to the task to be performed [20,21], interest in learning actions that lead to the achievement of didactic objectives [22], attraction to learning that favors the achievement of skills [23], social skills required to interact effectively in group practices [24], and improvement of student behavior and attitude [25].…”
Section: Gamification As a Learning Strategymentioning
confidence: 99%
“…In addition, the interactive process that occurs between the agents involved in the educational process [26] and the collaboration between these same agents [27] are benefited. It also increases factors that are influential in the maturational development of the student, such as motivation [28], a positive attitude towards learning [29], interest in knowing their own training [30], the autonomy of the student [31], commitment to the educational act [32], dedication to teaching by teachers and learning by students [33,34], as well as attraction, enjoyment, absence of negative feelings and the satisfaction of facing the task [35,36].…”
Section: Gamification As An Innovate Toolmentioning
confidence: 99%
“…With gamification, students prepare their own knowledge structures supported by academic indicators benefited such as motivation (Pisabarro and Vivaracho, 2018;Groening and Binnewies, 2019), attitude (Lee et al, 2013;Pérez-Manzano and Almela-Baeza, 2018), interest, autonomy (Xi and Hamari, 2019), commitment (Chu and Hung, 2015), dedication (Simões et al, 2013;Wang, 2015), attraction (Area and González, 2015), collaboration (Perrotta et al, 2013), interactions between agents (teacher-students and content) (Parra-González and Segura-Robles, 2019), and problem-solving capacity (Kapp, 2012) in activities to develop.…”
Section: Introductionmentioning
confidence: 99%